Proposed strategy through product rejuvenation in order for Post-it® 3”x3” classic color notes to increase performance in a competitive market - Firmansyah, Erick; Toha, Mohamad (The Indonesian Journal of Business Administration, 2018)
Abstract - Post-it® has been operating in Indonesia since 2003 with its office in Jakarta and its manufacturing warehouse in Tambun, Bekasi. Its core product is consumer product within the stationery industry, producing a well-known worldwide product, one of them are Post-it® sticky notes.  From 2012 up until 2016 is considered as a challenging year for Post-it® Indonesia where Indonesia’s economic slowdown and the increasing of import duty have caused its 3”x3” classic color notes sales to decline. Therefore the objectives of this research is to find the right business strategy for the company and to develop a strategic initiatives to help implement the business strategy. After analyzing the internal as well as the external environment of the company through interviews with the customers to define the customers buying criteria and the representatives of outlets where the product is sold, eventually the root causes of this problem were found and they are: lack of thorough knowledge on the customers, intense price competition from other lower priced competitors, technological threat from the digital version of sticky notes, and the increasing of importing duty. Solving these problems will potentially resolve the main problem. A good business strategy must be formulated by the company in order to solve these problems. Having conducted a thorough business strategy formulation, four alternatives strategies were generated and all the four strategies are expanding business coverage, rejuvenating existing packaging to a new smaller-sized packaging, creating a creativity application for smartphones to support the usage of sticky notes, and lastly create a collaboration between complementary brands to support each other as well as adding more value to the product. The implementation of these four strategies is conducted within short-term and long-term plan with continuous evaluation.Key words: business strategy, Post-it, sticky notes, 3M, stationery